A study of rainfall and floods in the Yamuna catchment (up to delhi) (MAUSAM, 1962)
The Yamuna which has been described in the Vedas (Bnrrard 1931) as one of the seven branches of the Gangs (Sapta-Sindhavas), drains the Punjab-11 umaon Himalayas from Simla in the northwest to Mussoorie in the southeast. In its Himalayan reach, its catch-ment lies between the two great Himalayan rivers, the Sutlej and the Ganga.